2020
DOI: 10.34172/aim.2020.68
|View full text |Cite
|
Sign up to set email alerts
|

Occult Hepatitis C Virus Infection among Hemodialysis Patients: An Iranian Experience

Abstract: Background: Patients with chronic kidney failure and those undergoing chronic hemodialysis (CHD) treatment are at high risk of infection with hepatitis C virus (HCV). The incidence of occult HCV infection (OCI) in CHD remains controversial and the real burden of HCV in this population may be affected by the rate of OCI. This study evaluates the molecular assessment of OCI in CHD in an Iranian population. Methods: All subjects on CHD in the South Khorasan province of Iran were invited for participation in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…They reported a rate of 3.36%, comparable to the current study's findings (18). The lowest prevalence of OCI in hemodialysis patients was reported by Eslamifar et al and Taherpour et al, who found prevalence rates of 0% and 1.6%, respectively (19,20). Compared to the study of Zahedi et al, in 2012, on the seroprevalence of HBV, HIV, and HCV among hemodialysis patients in Kerman, the prevalence of HCV among these patients decreased by 4% in this study (21).…”
Section: Discussionsupporting
confidence: 87%
“…They reported a rate of 3.36%, comparable to the current study's findings (18). The lowest prevalence of OCI in hemodialysis patients was reported by Eslamifar et al and Taherpour et al, who found prevalence rates of 0% and 1.6%, respectively (19,20). Compared to the study of Zahedi et al, in 2012, on the seroprevalence of HBV, HIV, and HCV among hemodialysis patients in Kerman, the prevalence of HCV among these patients decreased by 4% in this study (21).…”
Section: Discussionsupporting
confidence: 87%
“…It prolongs the life of patients with end-stage renal disease, improves their quality of life, and reduces death from uremia. [1][2][3] Among various comorbid illnesses associated with this problem, hypertension is mentioned as the main one. [4][5][6] According to the reports, 18-41% of patients with hypertension may need renal replacement therapy in the acute phase and the prevalence of hypertension varies from 70% to 90% among HD patients.…”
Section: Introductionmentioning
confidence: 99%